A method for preparing a reverse water gas shift catalyst and its application
By using the method of using the co -sedimentation method loading copper under the visible light assistance, prepare a high -efficiency anti -water gas transformation catalyst, solve the problem of low CO conversion efficiency in the existing technology, and achieve excellent CO conversion rate and high selectivity. Essence
Patent Information
- Application Number
- CN202410556160.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2023-11-22
- Filing Date
- 2024-05-07
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-05-07
AI Technical Summary
The prior art is difficult to efficiently activate the C=O bond of carbon dioxide, resulting in low CO conversion efficiency and unable to effectively solve the problems of greenhouse effects and energy demand.
Under the use of visible optical assistance conditions, the co -sedimentation method load copper is used to prepare inverse water gas transformation catalysts on the carrier material, improve the separation efficiency of photochemical electrons and holes, and separates thermal electrons through the CU LSPR effect for separation and transfer.
The yield and conversion rate of CO are significantly improved. The catalyst has excellent CO conversion rate and CO selectivity close to 100%, providing a new RWGS reaction strategy.
Smart Images

Figure CN118477652B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalyst synthesis, and in particular to a method for preparing a reverse water-gas shift catalyst and application thereof. Background Art
[0002] With the development of industry and the increasing intensity of human activities, the concentration of carbon dioxide (CO) in the global atmosphere has increased year by year. As the main component of greenhouse gases, the concentration of CO in the atmosphere has continued to rise, causing a series of severe environmental problems such as climate warming, glacier melting and ocean acidification, which seriously threaten the human living environment. At present, fossil fuels are still the main way for humans to obtain primary energy. Renewable energy such as solar energy and wind energy are still in the development stage and it is difficult to completely replace fossil fuels. CO is a single carbon structural unit that is abundant, cheap, non-toxic, non-flammable and renewable, and can be used as a good carbon source. Therefore, in addition to the development of new energy sources, carbon capture and storage (CCS) and carbon capture and utilization (CCU) technologies have attracted great attention because of their high efficiency and easy application to capture large amounts of CO.
[0003] The main ways to utilize CO include biological utilization, mineralization utilization, chemical synthesis, etc. Among the many CO utilization technologies, CO has attracted extensive attention from researchers by producing a variety of high-value basic chemicals through catalytic conversion. The main catalytic conversion technologies of CO include thermal catalysis, photocatalysis, and electrocatalysis. The research on catalytic conversion of CO mainly focuses on catalytic hydrogenation of CO.
[0004] However, whether from the perspective of environmental protection or CO utilization, catalytic hydrogenation of CO is a promising method for reducing the greenhouse effect and providing energy resources. However, CO has a very stable C=O bond and is thermodynamically difficult to activate. Researchers have tried to reduce the activation energy of CO reduction reaction by adding catalysts to achieve the goal of efficient conversion of CO. Therefore, the preparation of simple and easy-to-synthesize high-activity catalysts to convert carbon dioxide into CO and then produce high-value-added products is of great significance for improving the natural environment and solving energy needs. Summary of the invention
[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a method for preparing a reverse water-gas shift catalyst and its application. The present invention improves the CO yield compared to thermal catalysis by catalyzing the reverse water-gas shift reaction under visible light-assisted conditions, which is superior to most metal-based catalytic materials reported in the literature. The catalyst of the present invention loads copper on a carrier material by a co-precipitation method. The carrier material is reported for the first time and has the advantages of simple preparation steps, easy availability of raw materials, and safe operation. Characterization proves that the addition of Cu can improve the separation efficiency of photogenerated electrons and hole pairs, and the hot electrons generated by the LSPR effect of Cu can be effectively separated and transferred, which is the main factor for the catalytic material to have good photocatalytic performance. In addition, under light conditions, the catalyst is mainly based on the formate path. This work provides a new RWGS reaction strategy. At the same time, the catalyst obtained by the present invention has excellent CO conversion rate and CO selectivity close to 100%.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] A method for preparing a reverse water gas shift catalyst comprises the following steps:
[0008] S1. Add deionized water to a beaker, weigh the metal oxide precursor, molybdenum oxide precursor and citric acid and dissolve them in the beaker to obtain a mixed solution A;
[0009] S2. adjusting the pH value of the mixed solution A to 0.5-1.5 with an acidic solution;
[0010] S3. The mixed solution A after step S2 was heated and stirred in a water bath until it reached a gel state, dried overnight, and then calcined in a muffle furnace for 3-4h to obtain a carrier material;
[0011] S4. Weigh the support material of S3 and dissolve it in deionized water to obtain a support solution, then weigh the copper precursor and dissolve it in deionized water, and add the aqueous solution dropwise to the support solution to obtain a mixed solution B;
[0012] S5. Control the pH value of the mixed solution B to 8-10 with an alkaline solution;
[0013] S6. The mixed solution B treated in step S5 is aged, filtered, washed, dried, and calcined to obtain the reverse water gas shift catalyst.
[0014] Preferably, in S1, the mass ratio of the metal oxide precursor to the molybdenum oxide precursor is 10:1; and the molar ratio of the citric acid to the total metal atoms in the mixture of the metal oxide precursor and the molybdenum oxide precursor is 1:1.
[0015] Preferably, in S1, the molybdenum oxide precursor is one or more of ammonium molybdate or molybdic acid; the metal oxide precursor is one or more of cerium nitrate, cerium acetate, cerium chloride, cerium sulfate, gallium nitrate, gallium acetate, gallium chloride, gallium sulfate, titanium nitrate, titanium acetate, titanium chloride, and titanium sulfate.
[0016] Preferably, in S2, the acidic solution is an aqueous solution of one or more acids selected from hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid, carbonic acid, citric acid, tartaric acid, malic acid, perchloric acid, and hypochlorous acid; and the mass fraction of the acidic solution is 5%-25%.
[0017] Preferably, in S3, the temperature range of the water bath heating is limited to 60-80°C; the temperature range of the muffle furnace calcination is limited to 350-500°C.
[0018] Preferably, in S4, the copper precursor is one or more of copper sulfate, copper nitrate, copper chloride, copper carbonate, and copper acetate; and the mass fraction of the copper precursor is 5%-20%.
[0019] Preferably, in S5, the alkaline solution is one or more aqueous solutions of sodium hydroxide, potassium hydroxide, sodium carbonate, sodium bicarbonate, and ammonia.
[0020] Preferably, in S6, the aging time is limited to 4-8 hours; the drying temperature is limited to 90-110°C; the drying time is limited to 12-24 hours; the calcination temperature is limited to 400-800°C; and the calcination time is limited to 4-8 hours.
[0021] A use of a reverse water gas shift catalyst prepared according to the reverse water gas shift catalyst preparation method in a reverse water gas shift reaction.
[0022] Preferably, the application process is:
[0023] i. A fixed bed reactor is used as an evaluation device for the catalyst reaction activity, wherein the reaction tube is made of quartz glass;
[0024] ii. The catalyst was tableted and sieved, and 40 to 60 mesh reverse water gas shift catalyst particles were selected. 0.1 g of reverse water gas shift catalyst was weighed and mixed with 0.6 g of quartz sand and loaded into a quartz tube to be tested;
[0025] iii. Open the corresponding cylinders and hydrogen and air generators, start the computer, control the gas flow into the reaction system through the mass flow meter, then purge the reaction pipeline with nitrogen to remove air and check for leaks;
[0026] iv. Turn on the program temperature riser, raise the temperature to the specified reduction temperature at a heating rate of 10°C / min, and then reduce the calcined sample at 600°C for 1 hour through a certain flow of hydrogen;
[0027] v. Turn on the argon gas and the gas chromatograph. After the column box temperature and the detector temperature reach 80°C and 140°C respectively, turn on the TCD detector and set the bridge current to 50 mA;
[0028] vi. After the reduction is completed, nitrogen is introduced to purge down to the reaction temperature, and then the reaction raw material gas is opened to start the reaction, and the reaction product is detected and analyzed online by gas chromatograph.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] 1. The catalyst of the present invention loads copper on a carrier material by a coprecipitation method. The carrier material is reported for the first time and has the advantages of simple preparation steps, easy availability of raw materials, and safe operation. At the same time, the addition of Cu can improve the separation efficiency of photogenerated electrons and hole pairs, and the hot electrons generated by the LSPR effect of Cu can be effectively separated and transferred; the catalyst obtained by the present invention has an excellent CO conversion rate and a CO selectivity close to 100%;
[0031] 2. The catalyst prepared by the present invention mainly uses the formate pathway under light conditions, providing a new RWGS reaction strategy. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 The present invention is a flow chart of the preparation process of the reverse water gas shift catalyst;
[0033] Figure 2 The XRD diagram of the reverse water gas shift catalyst prepared in the present invention: wherein Cu / MoCe, Cu / MoTi, and Cu / MoGa correspond to the catalysts prepared in Example 1, Example 2, and Example 3, respectively;
[0034] Figure 3 This is a detection diagram of the CO2 conversion rate of the reverse water gas shift catalyst prepared by the present invention: wherein Cu / MoCe, Cu / MoTi, and Cu / MoGa correspond to the catalysts prepared in Example 1, Example 2, and Example 3, respectively;
[0035] Figure 4 This is a CO selectivity detection diagram of the reverse water gas shift catalyst prepared in the present invention: wherein Cu / MoCe, Cu / MoTi, and Cu / MoGa correspond to the catalysts prepared in Example 1, Example 2, and Example 3, respectively;
[0036] Figure 5This is a H2-TPR characterization analysis diagram of the reverse water-gas shift catalyst prepared in the present invention: wherein Cu / MoCe, Cu / MoTi, and Cu / MoGa correspond to the catalysts prepared in Example 1, Example 2, and Example 3, respectively;
[0037] Figure 6 This is a CO2-TPD characterization analysis diagram of the reverse water-gas shift catalyst prepared in the present invention: wherein Cu / MoCe, Cu / MoTi, and Cu / MoGa correspond to the catalysts prepared in Example 1, Example 2, and Example 3, respectively;
[0038] Figure 7 The XPS characterization analysis diagram of the reverse water gas shift catalyst prepared by the present invention: full spectrum (a), O1s after reduction (b), Mo 3d before reduction (c), Mo 3d after reduction (d), Cu 2p before reduction (e), Cu 2p after reduction (f); Cu / MoCe, Cu / MoTi, Cu / MoGa correspond to the catalysts prepared in Example 1, Example 2 and Example 3, respectively;
[0039] Figure 8 This is an in-situ DRIFTS study effect diagram of the reverse water gas shift catalyst prepared by the present invention;
[0040] Fig. 9 The catalytic cycle diagram of the RWGS reaction mechanism of the reverse water gas shift catalyst prepared in the present invention. DETAILED DESCRIPTION
[0041] The present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0042] See also Figure 1-9 , the present invention provides a technical solution:
[0043] Embodiment 1:
[0044] A method for preparing a reverse water gas shift catalyst:
[0045] With MoCe bimetallic material as carrier, 5 mL of deionized water was added to a beaker, 0.2483 g of cerium nitrate and 2.4752 g of ammonium molybdate were weighed and dissolved in the beaker, and then 3.4204 g of citric acid was weighed and added to the beaker (the molar ratio of citric acid to metal atoms was 1:1), and after stirring evenly, the pH value of the solution was adjusted to 1 with 5 mol / L nitric acid solution. The obtained mixture solution was then heated and stirred in a 70°C water bath until it reached a gel state, and then dried in a constant temperature oven at 100°C for 24 hours. The obtained sample was placed in a muffle furnace at 400°C in an air atmosphere and calcined for 3 hours, and then reduced by hydrogen to obtain MoCe as a carrier material.
[0046] Prepared by co-precipitation method. First, weigh 1g of carrier material and dissolve it in 30mL of deionized water (referred to as solution 1), then weigh 0.2046g of 5% copper nitrate by mass and dissolve it in 12.5mL of deionized water, and drop the aqueous solution of copper nitrate into solution 1. When dropping the copper nitrate solution, use 0.5mol / L sodium carbonate solution to control the pH to about 9. The obtained precipitate is aged at room temperature for 4h, then filtered, and washed with 500mL of deionized water, and then the obtained precipitate is dried in an oven at 100°C for 24h. The obtained solid sample is calcined in an air atmosphere at 600°C for 4h to obtain the catalyst Cu / MoCe.
[0047] Embodiment 2:
[0048] A method for preparing a reverse water gas shift catalyst:
[0049] With the MoTi bimetallic material as the carrier, 5 mL of deionized water was added to a beaker, 0.2345 g of titanium nitrate and 2.2476 g of ammonium molybdate were weighed and dissolved in the beaker, and then 3.0654 g of citric acid was weighed and added to the beaker (the molar ratio of citric acid to metal atoms was 1:1), and after stirring evenly, the pH value of the solution was adjusted to 1 with a 5 mol / L nitric acid solution. The obtained mixture solution was then heated and stirred in a 70°C water bath to a gel state, and then dried in a constant temperature oven at 100°C for 24 hours. The obtained sample was placed in a muffle furnace at 400°C in an air atmosphere and calcined for 3 hours, and then reduced by hydrogen to obtain a MoTi carrier material.
[0050] Prepared by co-precipitation method. First, weigh 1g of the carrier material obtained in the first step and dissolve it in 30mL of deionized water (called solution 2), then weigh 0.2046g of copper nitrate with a mass fraction of 5% and dissolve it in 12.5mL of deionized water, and drop the aqueous solution of copper nitrate into solution 2. When dropping the copper nitrate solution, use 0.5mol / L sodium carbonate solution to control the pH to about 9. The obtained precipitate is aged at room temperature for 4h, then filtered, and washed with 500mL of deionized water, and then the obtained precipitate is dried in an oven at 75°C overnight. The obtained solid sample is calcined in an air atmosphere at 600°C for 4h to obtain the catalyst Cu / MoTi.
[0051] Embodiment 3:
[0052] A method for preparing a reverse water gas shift catalyst:
[0053] Using MoGa bimetallic material as carrier, add 5mL deionized water to a beaker, weigh 0.2346g of gallium nitrate and ammonium molybdate and dissolve them in the beaker, then weigh citric acid and add it to the beaker (the molar ratio of citric acid to metal atoms is 1:1), stir evenly, and adjust the pH value of the solution to 0.5 with an appropriate amount of nitric acid solution. Then, heat and stir the obtained mixture solution in a 60°C water bath until it is in a gel state, and then dry it in a constant temperature oven at 120°C overnight. The obtained sample is placed in a muffle furnace at 450°C and calcined in an air atmosphere for 3 hours, and then reduced by hydrogen to obtain MoGa as a carrier material.
[0054] Prepared by co-precipitation method. First, weigh 1g of the carrier material obtained in the first step and dissolve it in 30mL of deionized water (called solution 2), then weigh 0.2046g of copper nitrate with a mass fraction of 5% and dissolve it in 12.5mL of deionized water, and drop the aqueous solution of copper nitrate into solution 2. When dropping the copper nitrate solution, use 0.5mol / L sodium carbonate solution to control the pH to about 9. The obtained precipitate is aged at room temperature for 1h, then filtered, and washed with 500mL of deionized water, and then the obtained precipitate is dried in an oven at 100℃ for 24 hours, and the obtained solid sample is calcined in an air atmosphere at 600℃ for 4h to obtain the catalyst Cu / MoGa.
[0055] The reverse water gas shift catalysts prepared in Examples 1-3 were subjected to XRD analysis, CO2 conversion analysis, CO selectivity analysis, H-TPR characterization analysis, CO-TPD characterization analysis, and XPS characterization analysis, and the results are as follows: Figure 2-7 As shown:
[0056] XRD analysis:
[0057] like Figure 2As shown in the figure, the crystal characteristics of the prepared Cu / MoCe, Cu / MoTi, and Cu / MoGa catalysts were characterized by XRD. The XRD diffraction patterns of the three catalysts all show obvious characteristic crystal peaks of MoO (PDF#05-0508), indicating that the crystallinity of MoO is high. No characteristic peaks of CuO were found in the XRD diffraction patterns of the three catalysts. However, new diffraction peaks appeared in the Cu / MoCe, Cu / MoTi, and Cu / MoGa catalysts. Looking up the PDF card database, Cu / MoCe has peaks corresponding to the CuMoO of PDF#22-0242 at 20=16.0°, 23.9°, 26.5°, and 33.0°; Cu / MoTi has peaks corresponding to the CuMoO of PDF#22-0242 at 20=23.9°, 26.5°, and 33.0°. There are differences in the diffraction intensities of the three catalysts, and the overall diffraction intensity of Cu / MoTi is greater. Table 1 shows the grain size data of the characteristic crystal plane of the catalyst. The grain size of Cu / MoCe, Cu / MoTi, and Cu / MoGa catalysts at the (020) crystal plane of 12.8° was calculated by the Sherrer formula. It was found that after the introduction of Cu, the grain size of Cu / MoCe and Cu / MoGa catalysts became smaller than that of the carrier, and the MoO3 crystallinity in Cu / MoCe was the lowest. It may be that the CuMoO generated by the introduction of Cu makes MoO more dispersed. The grain sizes of CuMoO of Cu / MoCe, Cu / MoTi, and Cu / MoGa catalysts at the overlap of 20=26.5°(040) crystal plane are 36.4nm, 57nm, and 41.2nm, respectively, indicating that the CuMoO formed in Cu / MoCe is well dispersed.
[0058] Table 1. Crystal size data of catalysts on different crystal planes
[0059]
[0060] CO2 conversion rate analysis:
[0061] In a fixed bed reactor, the effects of three catalysts on the catalytic activity of the reverse water gas shift reaction were studied. The gas content was detected online by gas chromatograph. The test results are as follows: Figure 3 As shown: Figure 3 The carbon dioxide conversion rate is hydrogen: carbon dioxide = 4:1. It can be seen from the figure that the reaction temperature of the three catalyst pairs increases from 200°C to 450°C, and the carbon dioxide conversion rate increases accordingly. This is because the reverse water gas shift reaction is an endothermic reaction, and an increase in temperature will promote the forward reaction.
[0062] CO Selectivity Analysis:
[0063] Figure 4The carbon monoxide selectivity is hydrogen: carbon dioxide = 4:1. It can be seen from the figure that when the reaction temperature of the three catalyst pairs increases from 200°C to 450°C, the carbon monoxide selectivity is close to 100%.
[0064] H-TPR characterization analysis:
[0065] H-TPR was used to characterize the reduction of Cu / MoCe, Cu / MoTi and Cu / MoGa catalysts, such as Figure 5 As shown in the figure, the three catalysts have a broad hydrogen consumption peak in the temperature range of 100-900℃, Cu / MoCe, Cu / MoTi and Cu / MoGa have small shoulder peaks at 440℃, 450℃ and 455℃, respectively, and strong main peaks at 566℃, 525℃ and 515℃. The shoulder peak at low temperature corresponds to the Cu in CuMoO. 2+ Partial reduction to form Cu + and MoO precipitation, the main peak represents Cu + The mixture formed by Cu / MoCe and MoO is reduced to metallic Cu and MoO. The main peak of Cu / MoCe appears at a higher temperature than that of other catalysts, indicating that the interaction between Cu and the support is stronger. Compared with the reduction of CuO at low temperature, the Cu in CuMoO 2+ and Cu + Complete reduction to metallic Cu occurs above 400°C, and the Mo in CuMoO + MoO is formed by H reduction at 450–550 °C. Compared with the individual oxides, the observed Cu in CuMoO 2+ and the reduction temperature of Cu1 increases and Mo + The reduction temperature of Cu is lowered. This may be related to the stability of Cu ions in the complex oxide structure and the H overflow reduction of Mo oxide on the copper particles formed during the reduction process. No reduction peak for Cu appears above 600℃, which can be determined as Cu 2+ is completely reduced to metallic Cu. These phenomena indicate that the incorporation of Cu to form CuMo oxide promotes the + The reduction of Mo may form more oxygen vacancies. However, Mo also makes Cu ions more stable, and the interaction between Cu and Mo affects the catalytic activity. The H consumption of the catalyst obtained by integrating the reduction main peak is shown in Table 2. The H consumption of Cu / MoCe, Cu / MoTi and Cu / MoGa catalysts is: 9.44mmol / g cat 、11.63mmol / g ca t, 10.48mmol / g cat. Combined with Table 2, the H consumption of the three catalysts increased after Cu loading, indicating that the catalysts have more oxygen-containing compounds reduced. After reduction, more oxygen vacancies are formed, thereby improving the adsorption and activation of CO and making the RWGS reaction activity better. The H consumption of Cu / MoTi is the highest, which may be because the Ti-doped MoTi structure has the best oxygen vacancy formation ability. The introduction of Cu further improves the oxygen vacancy formation ability and H consumption ability.
[0066] Table 2. H2-TPR and CO2-TPD data of catalysts
[0067]
[0068] CO-TPD characterization analysis:
[0069] CO is one of the reactants of RWGS, and CO is an acidic species. The alkalinity of the catalyst surface will affect the performance of the catalyst in the RWGS reaction. The desorption amount of CO is usually related to the concentration of alkaline sites, and the desorption temperature of CO can reflect the strength of the alkaline sites. The CO desorption ability and surface alkalinity strength of Cu / MoCe, Cu / MoTi and Cu / MoGa catalysts were studied by CO-TPD characterization. Figure 6 As shown. When the active metal Cu is introduced into different supports, the catalysts show different CO desorption abilities. According to the temperature zone of CO desorption, the alkalinity strength can be divided into three regions: weak alkaline sites (α) in the range of less than 350°C, medium alkaline sites (β) in the range of 350-600°C, and strong alkaline sites in the range of greater than 600°C. All three catalysts show two broad peaks in the temperature range of 100-600°C, indicating that the alkaline sites of the catalysts are concentrated in the weak alkaline and medium alkaline regions. The quantitative data and peak positions of the alkaline sites are shown in Table 2. The order of desorption temperature at the weak alkaline site is Cu / MoTi>Cu / MoGa>Cu / MoCe; the order of desorption temperature at the medium alkaline site is Cu / MoGa>Cu / MoTi>Cu / MoCe. The peak area of the CO desorption peak is always related to the amount of adsorbed CO, thereby indirectly reflecting the number of CO adsorption active sites on the surface of the catalyst under study. The amount of CO adsorbed by the three catalysts was obtained by integrating the CO desorption peak area. The CO adsorption amounts of the three catalysts, Cu / MoCe, Cu / MoTi and Cu / MoGa, were 0.25, 0.16 and 0.20 mmol CO2 / g, respectively. catThis indicates the number of CO adsorption active sites on the Cu / MoCe surface, which is beneficial to the adsorption and activation of more CO molecules, thereby improving the performance of the corresponding catalyst in the CO catalytic hydrogenation reduction reaction. The order of CO adsorption amount at weak basic sites is Cu / MoCe < Cu / MoTi < Cu / MoGa, and the order of CO adsorption amount at medium basic sites is
[0070] Cu / MoCe > Cu / MoTi > Cu / MoGa. The different amounts of CO adsorbed by the catalyst at different basic sites indicate that the environment for the catalyst to adsorb CO will affect the performance of the catalyst.
[0071] XPS characterization analysis:
[0072] The elemental composition and chemical valence states of the Cu / MoCe, Cu / MoTi, and Cu / MoGa catalysts before reduction and after reduction at 600 °C were characterized by XPS. As Figure 7 shown, the binding energy of the XPS spectra obtained was corrected by the binding energy of C1s at 284.8 eV. From Figure 7 the full XPS spectrum in a, it can be seen that there is a sharp peak corresponding to C1s, O 1s, Cu 2p, Mo 3d, Ce 3d, Ti 2p, and Ga 2p respectively, indicating that these elements exist in the corresponding catalysts respectively and no other heteroatoms appear. Figure 7 b is the XPS spectrum of O1s after reduction of the three catalysts. The peak at about 530.6 eV is related to lattice oxygen (OLatt), and the peak at about 531.5 eV is related to surface oxygen (Osur). The relative content of O1s obtained by integrating the peak area after fitting is shown in Table 3. The lower the surface oxygen content, the higher the oxygen vacancy content. The surface oxygen content of Cu / MoCe is the lowest, indicating that the surface oxygen is reduced to form more surface oxygen vacancies. Oxygen vacancies are beneficial to the adsorption and activation of CO, so it has excellent catalytic activity in the RWGS reaction.
[0073] Figure 7 c is the high-resolution XPS spectrum of Mo 3d before reduction. The spectra of the three catalysts all have two obvious peaks, which are the spin-orbit splitting of the Mo 3d energy level to produce Mo 3d5 / 2 and Mo 3d3 / 2, and there is an energy difference of 3.15 eV. The binding energies of Mo 3d in the Cu / MoCe, Cu / MoTi, and Cu / MoGa catalysts are 233.2 eV, 233.1 eV, and 233.0 eV respectively. These peaks correspond to Mo oxides with +6 valence ions. After the catalyst is reduced, the shape and position of the peaks change, as shown in 5 / d. The XPS spectrum of Mo 3d was fitted, mainly divided into Mo Figure 7 d. The XPS spectrum of Mo 3d was fitted, mainly divided into Mo + Mo + Mo +、Mo 0 The peak indicates that Mo + The relative contents of the four ions were obtained by integrating the peak areas of the Mo3dXPS spectrum after reduction, as shown in Table 3. Cu / MoCe, Cu / MoTi, Cu / MoGa catalysts Mo + The relative contents of Mo are 0.21, 0.23, and 0.27 respectively. 0 The contents of Cu / MoCe catalyst are 0.11, 0.12, and 0.09, respectively. The relative content represents the degree of Mo reduction. + ions are reduced to low-valent Mo ions. According to the analysis of O1s, Cu / MoCe has more surface oxygen vacancies, which may be related to Mo + It is related to the process of reduction to low-valent Mo ions.
[0074] The XPS spectra of Cu 2p of the three catalysts before reduction are as follows: Figure 7 As shown in e, the Cu 2p3 / 2 peak is fitted with two component peaks with different binding energies, corresponding to the surface Cu 2+ and Cu 0 It is worth noting that the significant vibration satellite peaks at 944.5eV for Cu / MoCe, 942.2eV for Cu / MoTi, and 962.7eV for Cu / MoGa are Cu 2+ The reduced Cu / MoCe peaks at 932.5eV and 952.3eV; Cu / MoTi peaks at 932.7eV and 952.5eV; Cu / MoGa peaks at 932.7eV and 952.5eV, and no significant vibration satellite peaks appear after reduction. These phenomena indicate that it may be Cu 2+ Reduction to Cu + or Cu 0 Combined with H-TPR, at 600℃, Cu 2+ Completely reduced to Cu 0 , so after reduction, Cu is Cu 0 Cu 0 It can also serve as an active site for CO, but too much Cu 0 Aggregation will lead to the weakening of the activity of RWGS reaction. 0 The XPS characteristic peak area integration is in the order of Cu / MoTi>Cu / MoCe>Cu / MoGa. 0 , so the catalytic activity of Cu / MoTi catalyst may decrease. 0 The active sites contribute to the adsorption and activation of CO2.
[0075] Table 3. XPS spectrum of the reduced catalyst. Relative contents of Mo3d and O1s
[0076]
[0077] Reaction path analysis of catalytic materials:
[0078] In order to gain a deeper understanding of the RWGS reaction on the catalytic material Cu / MoCe, in situ DRIFTS studies were performed, such as Figure 8 When the reaction gas is introduced into the sample tank under dark conditions, the -1 Two pairs of shoulder peaks were found at the product H2O, which are mainly attributed to the vibration of OH in the product H2O and Ce n+ -OH vibration mode, where Ce n+ The vibration of -OH is the main factor; at 2200-2400cm -1 The segment is attributed to the stretching vibration mode of C=O, which is attributed to the adsorption of CO2; -1 、2144cm -1 、2076cm -1 and 1950cm -1 Ce n+ adsorption of CO, physical adsorption of CO, linear adsorption of CO and isolated bridging; in addition, at 1420-1550cm -1 Section and 1340cm -1 The obvious stretching vibration peaks at the bottom belong to various carbonates and bicarbonates. It can be observed that under light-free conditions, as the temperature rises and the reaction proceeds, the vibration peak intensity of OH increases, which indicates that the increase in temperature promotes the production of H2O. However, compared with the spectrum under light conditions, it is found that the peak intensity of OH has obvious absorption at low temperatures. For the adsorption peak of CO, the CO adsorption peak that only appears at 400°C under light-free conditions appears at 350°C under light, which indicates that light effectively promotes the catalysis. The appearance of carbonate and bicarbonate peaks represents the appearance of carbonate or bicarbonate intermediates as the reaction proceeds. In addition, the stretching vibration peak of OCO is also found under light conditions, which is related to the formation of formate. Therefore, the illumination process helps to desorb the product in time at low temperatures. At the same time, through the exploration of intermediates, the reaction paths of the catalysts under light-free and light conditions are inconsistent.
[0079] For the RWGS reaction mechanism, the two widely recognized ones are redox mechanism and intermediate species decomposition mechanism. Combined with DRIFTS characterization, it is speculated that the catalytic material mainly follows the intermediate species decomposition mechanism, and the intermediate product under the condition of no light is carbonate, and the intermediate product under the condition of light is mainly carbonate and formates. Therefore, the following is proposed: Fig. 9 The possible catalytic cycle diagram is shown. After the catalyst is reduced, oxygen vacancies and low-valent metal active sites are formed. The light-irradiation process is mainly divided into seven reaction steps: (I) Hydrogen dissociates at the Cu site, and the dissociated H is filled in the oxygen vacancies through hydrogen overflow; (II) CO2 reacts with active oxygen to generate CO3 2- Intermediate species; (III) Migration of H species to generate HCO3 - Intermediate species; (IV) Migration and electrophilic addition of H species to generate HCOO - Intermediate species; (V) Reactive oxygen species fill oxygen vacancies; (VI) Intermediate species dissociate to release CO(g) and form Ce 4+ -OH; (VII) -OH reacts with H species to generate H2O and reforms oxygen vacancies. Under dark conditions, lower electron transfer makes HCO3 - Intermediate species tend to be more 0 The electrophilic addition to the surface directly decomposes to CO. However, HCO3 - The decomposition of Ce is still limited by temperature, which is also the reason why Ce n+ The main reason is that the vibration of -OH increases significantly with increasing temperature; the Cu + The linear adsorption of CO by species also hinders the desorption of CO.
[0080] The reverse water gas shift catalyst prepared by the prior art was selected as a comparative example, and its characterization results are shown in Table 4:
[0081] Table 4. Brief summary of RWGS reaction conditions of selected catalysts and their CO conversion and CO selectivity
[0082]
[0083]
[0084] The characterization data structures of the reverse water gas shift catalyst used as a comparative example are cited from the following references:
[0085] [1]Chen,X.;Su,X.;Liang,B.;Yang,X.;Ren,X.;Duan,H.;Huang,Y.;Zhang,T.Identification of relevant active sites and a mechanism study for reversewater gas shift reaction over Pt / CeO2 catalysts.J.Energy Chem.2016,25,1051-1057.
[0086] [4]Zhao,B.;Pan,Y.X.;Liu,C.J.The promotion effect of CeO2 on CO2adsorption and hydrogenation over Ga2O3.Catal.Today.2012,194,60-64.
[0087] [5]Panaritis,C.;Edake,M.;Couillard,M.;Einakchi,R.;Baranova,E.A.Insight towards the role of ceria-based supports for reverse water gasshift reaction over RuFe nanoparticles.J.CO2 Util.2018,26,350-358.
[0088] [6]Liu,Y.;Li,Z.;Xu,H.;Han,Y.Reverse water-gas shift reaction overceria nanocube synthesized by hydrothermal method.Catal.Commun.2016,76,1-6.
[0089] [8]Chen,L.;Wu,D.;Wang,C.;Ji,M.;Wu,Z.Study on Cu-Fe / CeO2 bimetalliccatalyst for reverse water gas shift reaction.J.Environ.Chem.Eng.2021,9,105183.
[0090] [9]Dai,H.;Zhang,A.;Xiong,S.;Xiao,X.;Zhou,C.;Pan,Y.The CatalyticPerformance of Ga2O3-CeO2Composite Oxides over Reverse Water Gas ShiftReaction.ChemCatChem.2022,14,e202200049.
[0091]
[13] Sun,F.M.;Yan,C.F.;Guo,C.Q.;Huang,S.L.Ni / Ce-Zr-O catalyst for highCO2 conversion during reverse water gas shift reaction(RWGS).Int.J.HydrogenEnergy.2015,40,15985-15993.
[0092]
[14] Lu,B.;Kawamoto,K.Preparation of mesoporous CeO2 and monodispersedNiO particles in CeO2,and enhanced selectivity of NiO / CeO2 for reverse watergas shift reaction.Mater.Res.Bull.2014,53,70-78.
[0093]
[15] Belekar,R.Suppression of coke formation during reverse water-gasshift reaction for CO2 conversion using highly active Ni / Al2O3-CeO2 catalystmaterial.Phys.Lett.A.2021,395,127206.
[0094]
[16] Li,S.;Xu,Y.;Chen,Y.;Li,W.;Lin,L.;Li,M.;Deng,Y.;Wang,X.;Ge,B.;Yang,C.Tuning the selectivity of catalytic carbon dioxide hydrogenation overiridium / cerium oxide catalysts with a strong metal-supportinteraction.Angew.Chem.2017,129,10901-10905.
[0095]
[17] Wang,W.;Zhang,Y.;Wang,Z.;Yan,J.M.;Ge,Q.;Liu,C.J.Reverse water gasshift over In2O3-CeO2catalysts.Catal.Today.2016,259,402-408.
[0096]
[33] Wang,L.C.;Khazaneh,M.T.;Widmann,D.;Behm,R.J.TAP reactor studiesof the oxidizing capability of CO on a Au / CeO catalyst-A first step towardidentifying a redox mechanism in the reverse water gas shiftreaction.J.Catal.,2013,302,20.
[0097]
[38] ·Liu,H.X.;Li,S.Q.;Wang,W.W.;Yu,W.Z.;Zhang,W.J.;Ma,C.;Jia,C.J.Partially sintered copper-ceria as excellent catalyst for the hightemperature reverse water gas shift reaction.Nat.Commun.,2022,13,867.
[0098]
[40] Matsubu,J.C.;Zhang,S.;Derita,L.;Marinkovic,N.S.;Chen,J.G.;Graham,G.W.;Pan,X.;Christopher,P.Adsorbate mediated strong metal supportinteractions in oxide supported Rh catalysts.Nat.Chem.,2017,9,120.
[0099]
[42] Li,W.;Gan,J.;Liu,Y.;Zou,Y.;Zhang,S.;Qu,Y.Platinum and FrustratedLewis Pairs on Ceria as Dual-Active Sites for Efficient Reverse Water-GasShift Reaction at Low Temperatures.Angew.Chem.Int.Ed.2023,62,e202305661.
[0100]
[44] Mine,S.;Yamaguchi,T.;Ting,K.W.;Maeno,Z.;Siddiki,S.M.A.H.;Oshima,K.;Satokawa,S.;Shimizu,K.;Toyao,T.Reverse water-gas shift reaction over Pt / MoO x / TiO2:reverse Mars-van Krevelen mechanism via redox of supportedMoO x .Catal.Sci.Technol.,2021,11,4172.
[0101]
[45] Chen,X.;Su,X.;Liang,B.;Yang,X.;Ren,X.;Duan,H.;Huang,Y.;Zhang,T.Identification of relevant active sites and a mechanism study for reversewater gas shift reaction over Pt / CeO catalysts.J.Energy Chem.,2016,25,1051.
[0102]
[46] Liu,Y.X.;Li,L.W.;Zhang,R.Y.;Guo,Y.H.;Wang,H.;Ge,Q.F.;Zhu,X.L.Synergetic enhancement of activity and selectivity for reverse water gasshift reaction on Pt-Re / SiO catalysts.J.CO Util.,2022,63,102128.
[0103]
[56] Bhalothia,D.;Yang,S.S.;Yan,C.;Beniwal,A.;Chang,Y.X.;Wu,S.C.;Chen,P.C.;Wang,K.W.;Chen,T.Y.Surface anchored atomic cobalt-oxide species coupledwith oxygen vacancies boost the CO-production yield of Pdnanoparticles.Sustain.Energy Fuels.2023,7,526.
[0104]
[59] Abdel-Mageed,A.;Wiese,K.;Hauble,A.;Bansmann,J.;Rabeah,J.;Parlinska-Wojtan,M.;Bruckner,A.;Behm,R.Steering the selectivity in COreduction on highly active Ru / TiO catalysts:support particle sizeeffects.J.Catal.,2021,401,160.
[0105]
[63] Vikanova,K.V.;Kustov,A.L.;Makhov,E.A.;Tkachenko,O.P.;Kapustin,G.I.;Kalmykov,K.B.;Mishin,I.V.;Nissenbaum,V.D.;Dunaev,S.F.;Kustov,L.M.Rhenium-contained catalysts based on superacid ZrO2 supports for CO2utilization.Fuel.2023,351,128956.
[0106]
[64] Rabee,A.;Zhao,D.;Cisneros,S.;Kreyenschulte,C.R.;Kondratenko,V.;Bartling,S.;Kubis,C.;Kondratenko,E.i V.;Brückner,Aa.;Rabeah,J.Role ofinterfacial oxygen vacancies in low loaded Au-based catalysts for the lowtemperature reverse water gas shift reaction.Appl.Catal.B-Env.,2023,321,122083.
[0107]
[72] Zhang,Z.Y.;Zang,Y.H.;Gao,F.;Qu,J.F.;Gu,J.F.;Lin,X.T.Enhancedcatalytic activity of CO hydrogenation to CO over sulfur-containing Ni / ZrOcatalysts:support size effect.New J.Chem.,2022,46,22332.
[0108]
[79] Kim,Y.;Kim,K.;Song,Y.;Lee,Y.;Roh,H.;Na,K.Highly CO-selective Ni-MgO-Ce x Zr 1-x O2 catalyst for efficient low-temperature reverse water-gas shiftreaction.Journal of Industrial and Engineering Chemistry.2023,118,341.
[0109]
[92] Kim,D.H.;Han,S.W.;Yoon,H.S.;Kim,Y.D.Reverse water gas shiftreaction catalyzed by Fe nanoparticles with high catalytic activity andstability.J.Ind.Eng.Chem.,2015,23,67.
[0110]
[101] Zhuang,Y.;Currie,R.;McAuley Kimberley B.;Simakov,D.S.A.Highly-selective CO2 conversion via reverse water gas shift reaction over the0.5wt%Ru-promoted Cu / ZnO / Al2O3 catalyst.Appl.Catal.A-Gen.2019,575,74.
[0111]
[104] Ebrahimi,P.;Kumar,A.;Khraisheh,M.Combustion synthesis of copperceria solid solution for CO2conversion to CO via reverse water gas shiftreaction.Int.J.Hydrogen Energy 2022,47,41259.
[0112]
[134] Okemoto,A.;Harada,M.R.;Ishizaka,T.;Hiyoshi,N.;Soto,K.Catalyticperformance of MoO3 / FAU zeolite catalysts modified by Cu for reverse watergas shift reaction.Appl.Catal.A-Gen.,2020,592,117415.
[0113]
[106] Zhang,L.;Yu,J.;Sun,X.;Sun,J.Engineering nanointerfaces of Cu-based catalysts for balancing activity and stability of reverse water gasshift reaction.J.CO Util.,2023,71,102460.
[0114]
[133] Zhang,R.;Wei,A.;Zhu,M.;Wu,X.X.;Wang,H.;Zhu,X.L.;Ge,Q.F.Tuningreverse water gas shift and methanation reactions during CO2 reduction on Nicatalysts via surface modification by MoO x .J.CO Util.,2021,52,101678.
[0115]
[139] Kharaji,A.G.;Shariati,A.;Takassi,M.A novelγ-Alumina supportedFe-Mo bimetallic catalyst for reverse water gas shift reaction.ChineseJ.Chem.Eng.,2013,21,1007.
[0116]
[138] Ronda-lloret,M.;Yang,L.Q.Q.;Hammerton,M.;Marakatti,V.S.;Tromp,M.;Sofer,Z.;Sepulveda-Escribano,A.;Ramos-Fernandez,E.V.;Delgado,J.J.;Rothenberg,G.;Reina,T.R.;Shiju,N.R.Molybdenum oxide supported on Ti3AlC2 is anactive reverse water gas shift catalyst.ACS Sustain.Chem.Eng.,2021,9,4957.
[0117]
[159] Yang,L.;Pastor-perez,L.;Gu,S.;Sepúlveda-Escribano,A.;Reina,T.R.Highly efficient Ni / CeO2-Al O catalysts for CO upgrading via reversewater gas shift:Effect of selected transition metal promoters.Appl.Catal.B-Environ.,2018,232,464.
[0118]
[161] Goguet, A.; Meunier, F.; Breen, J.; Burch, R.; Petch, M.; Faurghenciu, A. Study of the origin of the deactivation of a Pt / CeO catalyst during reversewater gas shift (RWGS) reaction. J. Catal., 2004, 226, 382.
[0119] By comparing the CO2 conversion rate and CO selectivity of the reverse water gas shift catalyst prepared in the present application, it can be seen that the CO2 conversion rate and CO selectivity of the reverse water gas shift catalyst prepared by the preparation method described in the present application are significantly better than most of the reverse water gas shift catalysts in the prior art, which strongly proves that the catalyst obtained in the present invention, based on the use of a new carrier material, still has an excellent CO conversion rate and a CO selectivity close to 100%, and has obvious application value and economic benefits.
[0120] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a reverse water gas shift catalyst, characterized in that: The following steps are involved: S1. Add deionized water to a beaker, weigh a metal oxide precursor, a molybdenum oxide precursor and citric acid, respectively, and dissolve them in the beaker to obtain a mixed solution A, wherein the metal oxide precursor is one or more of cerium nitrate, cerium acetate, cerium chloride, cerium sulfate, gallium nitrate, gallium acetate, gallium chloride, gallium sulfate, titanium nitrate, titanium acetate, titanium chloride, and titanium sulfate; S2. adjusting the pH value of the mixed solution A to 0.5-1.5 with an acidic solution; S3. The mixed solution A after step S2 was heated and stirred in a water bath until it reached a gel state, dried overnight, and then calcined in a muffle furnace for 3-4h to obtain a carrier material; S4. Weigh the support material of S3 and dissolve it in deionized water to obtain a support solution, then weigh the copper precursor and dissolve it in deionized water, and add the aqueous solution dropwise to the support solution to obtain a mixed solution B; S5. Control the pH value of the mixed solution B to 8-10 with an alkaline solution; S6. The mixed solution B after the treatment in step S5 is aged, filtered, washed, dried, and calcined, wherein the calcination temperature is limited to 400-800° C.; the calcination time is limited to 4-8 hours, to obtain the reverse water gas shift catalyst; In S1, the mass ratio of the metal oxide precursor to the molybdenum oxide precursor is 10:1; the molar ratio of the citric acid to the total metal atoms in the mixture of the metal oxide precursor and the molybdenum oxide precursor is 1:1; In S4, the copper precursor is one or more of copper sulfate, copper nitrate, copper chloride, copper carbonate, and copper acetate; and the mass fraction of the copper precursor is 5%-20%.
2. The method for preparing a reverse water gas shift catalyst according to claim 1, characterized in that: In S1, the molybdenum oxide precursor is one or more of ammonium molybdate or molybdic acid.
3. The method for preparing a reverse water gas shift catalyst according to claim 1, characterized in that: In S2, the acidic solution is an aqueous solution of one or more acids selected from hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid, carbonic acid, citric acid, tartaric acid, malic acid, perchloric acid, and hypochlorous acid; the mass fraction of the acidic solution is 5%-25%.
4. The method for preparing a reverse water gas shift catalyst according to claim 1, characterized in that: In S3, the temperature range of the water bath heating is limited to 60-80°C; the temperature range of the muffle furnace calcination is limited to 350-500°C.
5. The method for preparing a reverse water gas shift catalyst according to claim 1, characterized in that: In S5, the alkaline solution is one or more aqueous solutions of sodium hydroxide, potassium hydroxide, sodium carbonate, sodium bicarbonate, and ammonia.
6. The method for preparing a reverse water gas shift catalyst according to claim 1, characterized in that: In S6, the aging time is limited to 4-8 hours; the drying temperature is limited to 90-110° C.; and the drying time is limited to 12-24 hours.
7. Use of a reverse water gas shift catalyst prepared by the method for preparing a reverse water gas shift catalyst according to any one of claims 1 to 6 in a reverse water gas shift reaction.
8. Use of the reverse water gas shift catalyst according to claim 7 in a reverse water gas shift reaction, characterized in that: The application process is: i. A fixed bed reactor is used as an evaluation device for the catalyst reaction activity, wherein the reaction tube is made of quartz glass; ii. The catalyst was tableted and sieved, and 40 to 60 mesh reverse water gas shift catalyst particles were selected. 0.1 g of reverse water gas shift catalyst was weighed and mixed with 0.6 g of quartz sand and loaded into a quartz tube to be tested; iii. Open the corresponding cylinders and hydrogen and air generators, start the computer, control the gas flow into the reaction system through the mass flow meter, then purge the reaction pipeline with nitrogen to remove air and check for leaks; iv. Turn on the program temperature riser, raise the temperature to the specified reduction temperature at a heating rate of 10 °C / min, and then reduce the calcined sample at 600 °C for 1 hour through a certain flow of hydrogen; v. Turn on the argon gas and the gas chromatograph. After the column box temperature and the detector temperature reach 80°C and 140°C respectively, turn on the TCD detector and set the bridge current to 50mA; vi. After the reduction is completed, nitrogen is introduced to purge down to the reaction temperature, and then the reaction raw material gas is opened to start the reaction, and the reaction product is detected and analyzed online by gas chromatograph.
Citation Information
Cited By
Catalyst for reverse water gas shift reaction and preparation method thereof
CN122321845A
A catalyst for reverse water gas shift reaction and a method for preparing the same
CN122321845B